Environmental management systems : (Dansk standard, 1996)
The text of the international Standard ISO 14001:1996 has been prepared by Technical Commitee ISO/TC 207 "Environmental management" in collaboration with CEN/CS. this European Standard shall be given the status of a national standard, either by publication of an identicl text or by endorsement, at the latest by March 1997.